Kano Model Analysis for Measuring Visitor's Perception Towards Facility and Services in Teluk Penyu Tourism Area - Mohammad Dolla; Famila Dwi Winati; Fauzan Romadlon (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2022)
The current phenomenon is that many areas have the potential as tourist destinations but are not managed and equipped with proper facilities as tourist areas. Teluk Penyu is one of the tourism destinations that have the potential to develop. Therefore, improvements to the management of the Teluk Penyu need to be made to increase the interest of visiting tourists. This study uses the Kano Model, which focuses on the facilities and presents the Tourist Attraction Variable (A4), including accessibility, amenities, attractions, and ancillary. The results of this study indicate that the satisfaction attributes of A4 can be grouped into Kano's satisfaction category, namely one attribute in the must-be category, eight in one-dimensional, seven in attractive, and four in indifferent. Therefore, the priority for improvement starts from the must-be, one-dimensional, and attractive categories.